1997
DOI: 10.1021/ac9605307
|View full text |Cite
|
Sign up to set email alerts
|

Retention in Field-Flow Fractionation with a Moderate Nonuniformity in the Field Force

Abstract: In some field-flow fractionation (FFF) techniques, the basic analyte-field interaction parameter, λ, is not constant but varies within the channel cross section as a result of the nonuniformity of the force exerted by the field on the analyte. This is the case, for instance, in thermal FFF, because of the temperature dependence of the relevant physicochemical transport parameters. To account for this effect, a new FFF retention model is developed, allowing a linear variation of λ from the accumulation to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…(c) Perhaps there are experimental errors of unknown origin which cause systematic errors resulting in the gradient of the calibration line log Sλ vs log M to deviate from b. Alternatively Martin et al 29 have suggested that the deviations in b can be explained by simplifications made in the theoretical calculations.…”
Section: Resultsmentioning
confidence: 99%
“…(c) Perhaps there are experimental errors of unknown origin which cause systematic errors resulting in the gradient of the calibration line log Sλ vs log M to deviate from b. Alternatively Martin et al 29 have suggested that the deviations in b can be explained by simplifications made in the theoretical calculations.…”
Section: Resultsmentioning
confidence: 99%
“…It is also the elution time of an unretained compound. In thermal FFF, it has been shown that 2 can be expressed as [12,13]:…”
Section: Theorymentioning
confidence: 99%
“…The 2-value which is determined from the experimental measurement of the retention time in thermal FFF is thus an apparent value, )Lapp. Assuming that the rate of variation of 2 with x is approximately constant, at least in the vicinity of the accumulation wall, it has been shown that the position, Xeq, at which this apparent value is equal to the actual value of 2 is given by [14]:…”
Section: Theorymentioning
confidence: 99%
“…(6) and (7) and determined by solving Eq. (13), is associated with a welldefined value of x, the so-called equivalent position x eq , where the quantities (D/D T ), the local temperature T, and the local gradient (dT/dx) assume well-defined values, (D/D T ) eq , T eq , and (dT/dx) eq , respectively [11,14,21]. Moreover, this k quantity is linked to the quantities DT, T c , h c , and M according to Eq.…”
Section: General Aspects Of Thfffmentioning
confidence: 99%